PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAPKINERJA KARYAWAN PADA PT BERKAT CAHAYA NOVENA BOGOR - Zuprianus Zebua; Ahmad Syukri (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and discipline on employee performance at "PT Berkat Cahaya Novena Bogor". The method used in this research is a quantitative method. The total population in this study was 67 respondents. The sampling technique used saturated sampling and a sample of 67 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing. The results of this research are that the motivation variable partially has a positive and significant effect on employee performance with a calculated t value of (5,840 > 1.998) and a sig value of 0.000 < 0.05. This shows that H0 is rejected and H1 is accepted. The Work Discipline variable partially has a positive and significant effect on employee performance with a t value of (5,895 > 1.998) with a sig value of 0.000 <0.05. This shows that H0 is rejected and H2 is accepted. Based on the F (Simultaneous) hypothesis test, it can be seen that the F value is (23.315 > 3.140) and the significant value is 0.001 <0.05. So it can be concluded that H0 is rejected and H3 is accepted. This means that Motivation and Work Discipline simultaneously have a positive and significant effect on employee performance at PT Berkat Cahaya Novena Bogor. The R-Square is 0.421 or 42.1% and the remaining 57.9% is influenced by other variables not examined in the research. This